Prostaglandin E2 modulates presynaptic regulation of GnRH neurons via EP4 receptors in accordance with estrogen milieu. (30th September 2017) - Fujioka, Hitomi; Funabashi, Toshiya; Akema, Tatsuo
Highlights: PGE2 increased frequency, but not amplitude, of mEPSCs in GnRH neurons on the day of proestrus but not diestrus 1. PGE2 increased frequency, but not amplitude, of mEPSCs in GnRH neurons from OVX + E2 but not OVX + C rats. An EP4 agonist, but not EP1 or EP2 agonists, mimicked the effects on mEPSCs achieved by PGE2. Abstract: Prostaglandin E2 (PGE2) promotes gonadotropin secretion by regulating the activity of neurons that release gonadotropin-releasing hormone (GnRH) in the hypothalamus. However, the mechanisms of action of PGE2 at these neurons have yet to be fully explored. We examined the effects of PGE2 on the generation of miniature excitatory postsynaptic currents (mEPSCs) at GnRH neurons as measured by whole-cell, patch-clamp recordings. GnRH neurons were identified in slices prepared from the preoptic areas of female GnRH-EGFP rats. Exposure to PGE2 significantly increased the frequency, but not the amplitude, of the mEPSCs generated on the day of proestrus, but neither frequency nor amplitude was altered on day 1 of diestrus. These data suggest that the action of PGE2 on mEPSC frequency varies depending on the stage of estrous. An estrogen-dependence of PGE2's action was further supported by the increased frequency, but not amplitude, of mEPSCs generated at GnRH neurons prepared from estrogen-primed ovariectomized rats. Conversely, PGE2 had no effect on mEPSC frequency or amplitude at GnRH neurons in cholesterol-treated rats. Subsequent experiments to identify candidate receptors for PG2E's action revealed that exposure to a PGE2 receptor 4 (EP4) agonist, but not EP1 or EP2 agonists, mimicked the effects achieved by PGE2 exposure. These effects of mEPSCs could be reversed using an EP4 antagonist, illustrating the specificity of the effect. Collectively, these data demonstrate that PGE2 can alter excitatory synaptic neurotransmission at GnRH neurons via EP4 signaling at presynaptic site(s) in an estrogen-dependent fashion during proestrus.